The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/pssa.201026416
|View full text |Cite
|
Sign up to set email alerts
|

Integrated impedance based hydrocarbon gas sensors with Na‐zeolite/Cr2O3 thin film interfaces: Electrochemical mechanism of the impedance changes

Abstract: This study aims to clarify the mechanism of a hydrocarbon gas sensor effect, which involves impedance changes of a Na+ ion conducting Pt‐doped zeolite layer in contact with chromia (Cr2O3) films as electrodes. Based on our previous studies on sensing characteristics and model experiments with asymmetrical cells, a coherent picture of the sensing mechanism is derived: The impedance change is attributed to the process of Na+ ion insertion from the zeolite into the chromia film. The impedance of this interface pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The other group of molecules that has been extensively studied are hydrocarbons [ 58 60 ]. Impedance spectra of a device made by coating Cr 2 O 3 on top of an ion-conducting Pt-doped ZSM-5 exhibited several semicircles, with a hydrocarbon dependent semicircle in the medium frequency range [ 58 ] (though later studies from the same group showed that it is the low frequency part that exhibits the increase in the presence of the hydrocarbons) [ 59 , 61 ]. Measurements at a fixed frequency in the hydrocarbon sensitive region exhibited high sensitivity to different hydrocarbons and minimal interference to CO and H 2 , but with interference to NH 3 .…”
Section: Sensors Based On Intrazeolite Cation Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The other group of molecules that has been extensively studied are hydrocarbons [ 58 60 ]. Impedance spectra of a device made by coating Cr 2 O 3 on top of an ion-conducting Pt-doped ZSM-5 exhibited several semicircles, with a hydrocarbon dependent semicircle in the medium frequency range [ 58 ] (though later studies from the same group showed that it is the low frequency part that exhibits the increase in the presence of the hydrocarbons) [ 59 , 61 ]. Measurements at a fixed frequency in the hydrocarbon sensitive region exhibited high sensitivity to different hydrocarbons and minimal interference to CO and H 2 , but with interference to NH 3 .…”
Section: Sensors Based On Intrazeolite Cation Conductivitymentioning
confidence: 99%
“…An alternative explanation has also been proposed to explain the impedance changes of the zeolite/chromia device in the presence of hydrocarbons [ 61 ]. Sorption of gas within the zeolite pores is proposed to alter the electrochemical potential at the zeolite surface.…”
Section: Sensors Based On Intrazeolite Cation Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the ammonia sensor, it is obvious that the bulk properties change with ammonia adsorption [ 19 ], whereas in some hydrocarbon sensors, electrode/bulk interactions seem to play a major role [ 20 ]. The detailed effect remains a subject of discussion [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the formation of the potential difference U between both electrodes is under study and will explicitly not be discussed here. The interested reader is referred to the literature [ 21 , 22 , 27 ].…”
Section: Introductionmentioning
confidence: 99%